Childbirth fear, anxiety, fatigue, and sleep deprivation in pregnant women - Hall, W.; Hauck, Yvonne; Carty, E.; Hutton, E.; Fenwick, J.; Stoll, K. (2009)
Objective: To explore women's levels of childbirth fear, sleep deprivation, anxiety, and fatigue and their relationships during the third trimester of pregnancy. Design: A cross-sectional descriptive survey of a community sample. Participants: Six hundred and fifty English-speaking nulliparous and multiparous women, 17 to 46 years of age and between 35 and 39 weeks gestation, with uncomplicated pregnancies. Methods: Wijma Delivery Expectancy/Experience Questionnaire, Spielberger State Anxiety Inventory, Mindell's Sleep Questionnaire, and the Multidimensional Assessment of Fatigue Questionnaire. Results: Twenty-five percent of women reported high levels of childbirth fear and 20.6% reported sleeping less than 6 hours per night. Childbirth fear, fatigue, sleep deprivation, and anxiety were positively correlated. Fewer women attending midwives reported severe fear of childbirth than those attending obstetricians. Women with high childbirth fear were more likely to have more daily stressors, anxiety, and fatigue, as well as less help. Higher levels of anxiety predicted higher levels of childbirth fear among women. Conclusion: One fourth of women reported high childbirth fear. Women's fear of childbirth was related to fatigue, available help, stressors, and anxiety. Fear of childbirth appears to be part of a complex picture of women's emotional experiences during pregnancy. © 2009 AWHONN.